MATERNAL DEATH, QUALITY SERVICES, AND MENTAL HEALTH: A CYCLE OR REPEATED EPISODE ? - Nuzulul Kusuma Putri (Universitas Airlangga, 2022)
Maternal issues are classic issues in every edition of the Indonesian Journal of Health Administration. In this issue, our authors, Fatmaningrum et al. (2022), revealed how the COVID-19 pandemic had increased the number of maternal deaths. Research conducted by Ernawaty and Sri (2022) again shows how big the risks Indonesian women must bear during pregnancy and childbirth are. Not only are they risking their lives because they have to give birth to children, but once discharged from treatment, they still have to be faced with high delivery costs. The National Health Insurance does help a lot, but who will help JKN from a deficit if there are many cases of diseases that require huge costs. A systematic review conducted by Muhlis (2022) found that the low level of participation in the JKN program was due to various multidimensional factors. This factor is not only related to the ability to pay contributions, but many are due to individual and environmental internal factors.